2001
DOI: 10.1161/01.hyp.37.4.1047
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Angiotensin and Pathobiology of Vascular Disease

Abstract: Abstract-There is increasing evidence that direct pathobiological events in the vessel wall play an important role in vascular disease. An important mechanism involves the perturbation of the homeostatic balance between NO and reactive oxygen species. Increased reactive oxygen species can inactivate NO and produce peroxynitrite. Angiotensin II is a potent mediator of oxidative stress and stimulates the release of cytokines and the expression of leukocyte adhesion molecules that mediate vessel wall inflammation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
442
0
15

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 704 publications
(474 citation statements)
references
References 66 publications
13
442
0
15
Order By: Relevance
“…[37][38][39] ARBs, particularly telmisartan and olmesartan, also exert antidiabetic effects through their regulation of insulin sensitivity and reduce not only urinary albumin excretion but also urinary 8-OHdG and L-FABP excretion. 40 Statins have been shown to ameliorate tubular and podocyte injury, preserve GFR and reduce proteinuria in renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39] ARBs, particularly telmisartan and olmesartan, also exert antidiabetic effects through their regulation of insulin sensitivity and reduce not only urinary albumin excretion but also urinary 8-OHdG and L-FABP excretion. 40 Statins have been shown to ameliorate tubular and podocyte injury, preserve GFR and reduce proteinuria in renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Free radical induced oxidative stress in part contributes to endothelial dysfunction and development of hypertension [169]. Increased ROS generation eliminates NO • by forming ONOO -, thus reducing NO • bioavailability which leads to decreased endothelium-dependent vasodilation resulting in hypertension [170]. A decrease in NO bioavailability and an increase in oxidative stress are present in human hypertension [171].…”
Section: Hypertension (Ht)mentioning
confidence: 99%
“…67 NADPH oxidase is a multisubunit complex composed of cytosolic components, such as p47 phox , p67 phox and Rac 1, and membrane-spanning components, such as p22 phox and gp91 phox . The production of ROS by activated NADPH oxidase is mediated by several pathways.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…59,60,68 Ang II-induced NADPH oxidase activation is one of the major sources of ROS in atherosclerosis. 18,19,67,68 Zalba et al 68 showed that endothelial dysfunction is due to an excess of ROS rather than a decrease in NO production in the aorta of spontaneously hypertensive rats and is associated with both upregulation of p22 phox mRNA expression and increased activity of NADPH oxidase. Upregulation of p22 phox mRNA expression is a key component of Ang II-induced NADPH oxidase activation, and increased expression levels of other components also have an important role in this oxidase under pathological conditions.…”
Section: Oxidative Stressmentioning
confidence: 99%